Green Is Good Planning Urban Green Spaces With People, Not For People - Fakin Bajec, Jasna (ZRC SAZU, Založba ZRC, 2019)
This toolkit has been developed during the implementation of Urban Green Belts (UGB) project (Interreg, Central Europe) which main objective was to improve planning, management and decision-making capacities of the public sector related to urban green spaces, thus creating integrated sustainable UGS planning and management systems. Special attention was given to functional urban areas (FUA), a functional economic unit characterised by densely inhabited "urban cores" and "hinterlands" whose labour market is highly integrated with the cores. Following a comparative situation analysis, the partners jointly designed innovative methods and tools to facilitate sustainable UGS management. Presented toolkit has been primarily developed as a Model for a Community Involvement. The presented methods and tools for community building were tested in three pilot studies conducted in Maribor (Slovenia), Krakow (Poland), and Budapest (Hungary).